EmbrASD: Android Mobile Application for Children with Autism as a Supplemental Tool for Therapy - Aris E. Ignacio; Mark Angelo A. Ligot (Future Science, 2021)
Autism has a very wide range that influences people, specifically children in general. Usually, it affects a child’s social interaction, communication, behaviors, and interests. Providing a complete device for treatment which is planned to be used by kids with autism needs to be taken into consideration. There is no software available that will adhere to the main areas of autism. The development a multidimensional software that focuses the main areas of kids with autism was a specific goal that the paper is being addressed. It is planned from the viewpoint of several specialists: more particularly speech therapist, occupational therapist, Special Education (SPED) educator and an Applied Behavior Analysis (ABA) specialist. The specialists’ focused objectives were lengthily included into the planning of the software. The development of an application for the young with autism that would completely attend to all the main areas that are initiated by autism and serves as an addendum to treatment is the primary goal of the study. Interviews from, speech therapist, occupational therapist, SPED teacher, ABA therapist and a SPED therapist will serve as a basis and the prototyping methodology for system development. With the implemented system, the intended users gave an approval on the application to be integrated in the teaching of children with autism. Suggestions on the improvement of the application comprises of including video recording for API 22, implementing the system in the iOS environment, and concentration on older autism cases were recommended.